Application of phi (Φ), the golden ratio, in computing: a systematic review - Akhtaruzzaman, M; Tanvin, Jamal Uddin; Shafie, Amir Akramin; Shahryer, Fahim; Halder, Sachitra (IEEE, 2024)
The Golden Ratio (φ) has intrigued researchers for centuries due to its widespread presence in both nature and science. This article systematically examines φ’s diverse applications in computing, focusing on its role in enhancing visual appeal, optimizing algorithms, system design, and influencing fields such as biometrics, machine intelligence, and engineering. Through a systematic review of recent studies, this work aims to identify how φ can improve computational efficiency across various computing domains. The methodology involves a comprehensive analysis of cutting-edge research sourced from 12 reputable digital platforms to explore φ’s potential. This study highlights the versatility of Golden Ratio, as its applications and relationships were found to account for 51% and 49%, respectively, across a total of 51 selected studies from 27 countries spanning six continents. The review also categorizes findings by their specific applications and contexts, providing valuable insights into φ’s impact on mathematics, cryptography, search algorithms, machine learning, artificial intelligence, photonics, natural sciences, system design, power engineering, robotics, and practical human life. This study opens promising avenues for future research on the applications of φ in diverse fields of science, engineering, and computing.